British National Formulary for Children: the risk of inappropriate paracetamol prescribing. Issue 3 (1st October 2011) - Eyers, Sally; Fingleton, James; Eastwood, Ashley; Perrin, Kyle; Beasley, Richard
Abstract : Background: Paracetamol is the most commonly prescribed medicine for children. Age-based dosing guidelines can lead to inappropriate dosing. Methods: A review of age-based guidelines for paracetamol in the British National Formulary for Children (BNFC) 2011–2012 was undertaken. Single and cumulative daily doses of paracetamol for boys and girls at 9th, 50th and 91st centiles for weight were calculated for the age groups 1–3 months, 3–12 months, 1–6 years and 6–12 years. Results: For children at the 9th centile, aged 3 months and above, doses were above recommended single and cumulative daily dose therapeutic limits when given the highest dose specified for their age. For children at the 91st centile at all ages, doses were below recommended single and cumulative daily dose therapeutic limits when given the lowest dose specified for their age. Conclusions: Underweight and overweight children are at risk of inappropriate paracetamol administration based on BNFC age-based dosing instructions.